Physical activity, diet, and risk of Alzheimer disease. - Scarmeas, Nikolaos; Luchsinger, Jose A; Schupf, Nicole; Brickman, Adam M; Cosentino, Stephanie; Tang, Ming X; Stern, Yaakov (JAMA, 2009)
CONTEXT: Both higher adherence to a Mediterranean-type diet and more physical activity have been independently associated with lower Alzheimer disease (AD) risk but their combined association has not been investigated. OBJECTIVE: To investigate the combined association of diet and physical activity with AD risk. DESIGN, SETTING, AND PATIENTS: Prospective cohort study of 2 cohorts comprising 1880 community-dwelling elders without dementia living in New York, New York, with both diet and physical activity information available. Standardized neurological and neuropsychological measures were administered approximately every 1.5 years from 1992 through 2006. Adherence to a Mediterranean-type diet (scale of 0-9; trichotomized into low, middle, or high; and dichotomized into low or high) and physical activity (sum of weekly participation in various physical activities, weighted by the type of physical activity [light, moderate, vigorous]; trichotomized into no physical activity, some, or much; and dichotomized into low or high), separately and combined, were the main predictors in Cox models. Models were adjusted for cohort, age, sex, ethnicity, education, apolipoprotein E genotype, caloric intake, body mass index, smoking status, depression, leisure activities, a comorbidity index, and baseline Clinical Dementia Rating score. MAIN OUTCOME MEASURE: Time to incident AD. RESULTS: A total of 282 incident AD cases occurred during a mean (SD) of 5.4 (3.3) years of follow-up. When considered simultaneously, both Mediterranean-type diet adherence (compared with low diet score, hazard ratio [HR] for middle diet score was 0.98 [95% confidence interval CI, 0.72-1.33]; the HR for high diet score was 0.60 [95% CI, 0.42-0.87]; P = .008 for trend) and physical activity (compared with no physical activity, the HR for some physical activity was 0.75 [95% CI, 0.54-1.04]; the HR for much physical activity was 0.67 [95% CI, 0.47-0.95]; P = .03 for trend) were associated with lower AD risk. Compared with individuals neither adhering to the diet nor participating in physical activity (low diet score and no physical activity; absolute AD risk of 19%), those both adhering to the diet and participating in physical activity (high diet score and high physical activity) had a lower risk of AD (absolute risk, 12%; HR, 0.65 [95% CI, 0.44-0.96]; P = .03 for trend). CONCLUSION: In this study, both higher Mediterranean-type diet adherence and higher physical activity were independently associated with reduced risk for AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoproteins E; Body Mass Index; Comorbidity; Confounding Factors (Epidemiology); Depression; Diet, Mediterranean; Educational Status; Energy Intake; Female; Genotype; Humans; Leisure Activities; Male; Motor Activity; New York City; Primary Prevention; Proportional Hazards Models; Prospective Studies; Residence Characteristics; Risk Assessment; Risk Factors; Smoking